STRATEGIC ADAPTATION FEATURES AS FACTOR TO IMPROVE SYSTEM EFFICIENCY AT ENTERPRISE - Vladimir A. Saakyan (Вестник Северо-Кавказского федерального университета)
Implementation of strategic potential for an enterprise plays one of the priority roles in long-term functi0oning and development. When working under constantly changing external conditions, the agents of economic activity have to employ not just efficient adjustment methods yet also facilitate systematization of their performance. This article provides a view on the aspects related to balancing the systemic nature of business-processes and the optimal interaction with the unstable external surroundings.